Beispiel Nr: 18
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(2/0)\qquad Q(-\frac{2}{3}/0) \\\\ \\ \textbf{Rechnung:} \\ P(2/0)\qquad Q(-\frac{2}{3}/0) \qquad a=-2 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=-2(x-2)(x+\frac{2}{3})\\ y=-2(x^2+x \cdot \left(-2\right) +\frac{2}{3}\cdot x +\left(-2\right)\cdot \frac{2}{3} )\\ y=-2(x^2 -1\frac{1}{3} x-1\frac{1}{3}) \\ y= -2x^2+2\frac{2}{3}x+2\frac{2}{3} $